Fatal xylenol self-poisoning. Issue 727 (May 1986) - Watson, I. D.; McBride, D.; Paterson, K. R.
Abstract : A case of fatal xylenol ingestion by a long-stay mental hospital patient is described. The clinical course was similar to that observed in other phenolic poisonings with active bowel sounds, nausea and vomiting, severe metabolic acidosis, hypotension and cardiac and renal failure. The formulation of xylenol ingested contains alcohol which would facilitate absorption; due to the dangers of such poisonings care must be exercised as to access and exposure to xylenol sterilising agents.